Proposiiton 48--College Admissions Tests: Friend or Foe? - Kellenberger, Rosemary C. (My University, 1986)
This article reviews the background of college admissions tests, specifically the SAT and the ACT. The primary discussion refers to the SAT, though some discussion generalizes to the ACT. Whether or not admission test scores can properly be used for minority students, especially those involved in intercollegiate sports, is discussed. The special problems dealing with collegiate preparation, especially for blacks, are presented. The author critiques standardized tests as potentially harmful to Black students,also noting the high number of Black students requiring remedial education, a result of issues in the K-12 education system.
Keywords: academic predictors; eligibility; race; demographics